The impact of organic certification information on consumer's perceptions of organic products - Wong, David; Loh, Claire; Quintal, Vanessa (University of Western Sydney, 2008)
The Australian organic food industry is extremely dynamic in nature. From a consumer marketing perspective, an important area requiring further research is in the impact of organic certification on consumer product perceptions. This study examined the impact of organic certification, through the use of an experimental design, to measure consumer product perceptions derived from exposure to different levels of organic certification information on product labels. The analysis revealed organic certification information does impact ultimate consumer product perceptions - in particular with regards to the product's impact on the environment and its health benefits. Recommendations from this study include the importance of properly educating Australian consumers about organic certification, and developing consumer confidence in organic certification information.